FRI0716-HPR FACTORS WHICH IMPACT COMPLETION AND NON-COMPLETION OF PHYSICAL ACTIVITY INTERVENTIONS FOR PEOPLE WITH RHEUMATOID ARTHRITIS: A SYSTEMATIC REVIEW. (June 2019) - Reynolds, Niamh; Larkin, Louise
Abstract : Background: Rheumatoid arthritis (RA) is a systemic inflammatory condition which results in pain, fatigue, joint stiffness and an increased risk of cardiovascular issues. Physical activity (PA) has been proven to help reduce the severity of these symptoms and the risk of cardiovascular disease [1]. However, recent literature has shown that people with rheumatoid arthritis do not meet PA guidelines [2]. The systematic review aims to determine the factors which affect the completion rates of adults with RA in PA interventions. Objectives: 1) Review the effect of the frequency, intensity, time and type of exercise (FITT principle) on participation rates. 2) Review the reasons for dropping out of an intervention and consider how this can be avoided in planning future interventions. 3) Examine the effect of behaviour change techniques used on completion rates.4) Explore the effect of adverse outcomes on completion rates. Methods: A systematic review of the literature was carried out in February 2018. Inclusion criteria were: detailed intervention information, completion rates reported, published between 1998-2018 and published in English. Included papers were assessed using the Cochrane risk of bias tool by two assessors. The relevant data was then extracted, compared and conclusions were drawn. Results: Nine studies with varying levels of quality were included in this review. Reasons for not completing an intervention could be divided into modifiable and non-modifiable factors; modifiable factors include the FITT principle, the behaviour change component and controlling for adverse outcomes. Non-modifiable factors included the environment, illness/flare-up and accidents. The results found that when people with RA had an individualised PA program that started at a low-moderate intensity they had higher participation rates than those who followed a generalised program, with no behaviour change component. Altering the intervention in response to patient's pain levels improved completion rates of the intervention. Conclusion: When designing PA programs for people with RA, the EULAR PA guidelines for people who have inflammatory arthritis [3] should be followed. However, it should be noted that engagement and participation in PA interventions is increased when the intervention is of low impact PA and starts at a low-moderate intensity. Individualising the activity to the person and applying behaviour change techniques have also been found to improve participation. References: [1] Kerschan-Schindl, K. andMacHold, K. (2011) 'Rehabilitation von Patienten mit rheumatoider Arthritis', Physikalische Medizin Rehabilitationsmedizin Kurortmedizin, 21(6), pp.297–310. Doi: 10.4061/2011/681640. [2] Larkin, L. andKennedy, N. (2014) 'Correlates of Physical Activity in Adults with Rheumatoid Arthritis: A Systematic Review', Journal of Physical Activity and Health, 11(6), pp.1248–1261. Doi: 10.1123/jpah.2012-0194. [3] Rausch Osthoff, A. K. et al. (2018) '2018 EULAR recommendations for physical activity in people with inflammatory arthritis and osteoarthritis', Annals of the Rheumatic Diseases, 77(9), pp.1251–1260. Doi: 10.1136/annrheumdis-2018-213585. Disclosure of Interests: None declared